Associations between physical activity, basic motor competencies and automatic evaluations of exercise. Issue 16 (18th August 2021) - Mücke, Manuel; Ludyga, Sebastian; Andrä, Christian; Gerber, Markus; Herrmann, Christian
ABSTRACT: Dual process theories suggest that the decision to be physically active is influenced by reflective and automatic processes. However, associations of automatic (affective) evaluations of exercise with physical activity and underlying basic motor competencies have not yet been investigated in children and young adolescents. Ninety-one participants (52 male; age: 10–14 years) were recruited from academic high schools in Germany and Switzerland. Automatic evaluations of exercise were measured with the Single-Target Implicit Association Test (ST-IAT) and a D-score was calculated. Moderate-to-vigorous physical activity (MVPA) and vigorous physical activity (VPA) per day were determined via wrist-worn actigraphy over the course of seven days. Basic motor competencies were measured using the MOBAK-5 test battery. Pearson correlations showed non-significant associations of automatic evaluations of exercise with MVPA, but significant associations with VPA. Basic motor competencies were associated with automatic evaluations of exercise, and the MOBAK subscale of object movement was associated with both MVPA and VPA. Our results underscore the relevance of affective processes for physical activity behaviour. This could potentially be relevant for interventions targeting physical activity promotion. Longitudinal investigations and intervention studies are necessary to verify causal relationships and potential underlying mechanisms.